Combined methods to evaluate human cells in muscle xenografts. - Mona Bensalah; Pierre Klein; Ingo Riederer; Soraya Chaouch; Laura Muraine; Wilson Savino; Gillian Sandra Butler-Browne; Capucine Trollet; Vincent Mouly; Anne Bigot; Elisa Negroni (PLoS ONE, 2019)
Xenotransplantation of human cells into immunodeficient mouse models is a very powerful tool and an essential step for the pre-clinical evaluation of therapeutic cell- and gene- based strategies. Here we describe an optimized protocol combining immunofluorescence and real-time quantitative PCR to both quantify and visualize the fate and localization of human myogenic cells after injection in regenerating muscles of immunodeficient mice. Whereas real-time quantitative PCR-based method provides an accurate quantification of human cells, it does not document their specific localization. The addition of an immunofluorescence approach using human-specific antibodies recognizing engrafted human cells gives information on the localization of the human cells within the host muscle fibres, in the stem cell niche or in the interstitial space. These two combined approaches offer an accurate evaluation of human engraftment including cell number and localization and should provide a gold standard to compare results obtained either using different types of human stem cells or comparing healthy and pathological muscle stem cells between different research laboratories worldwide.